Candida albicans outbreak associated with total parenteral nutrition in the neonatal unit - SÜMBÜL, BİLGE; Güdücüoğlu, Hüseyin; Gultepe, BİLGE; OTLU, BARIŞ; BEKTAS, A.; YILDIRIM, OĞUZHAN; Tuncer, Oğuz; BERKTAS, M. (My University, 2016)
Background: The most frequently isolated fungi in patients using TPN belongs to the Candida genus. Various infections including venous catheter infections, fungemia, endocarditis and ophthalmitis may be encountered. Objective: Upon growth of Candida in the blood cultures from the pediatric (neonatal) unit of our hospital, a surveillance was performed in this unit and involving the health care workers. Clonal relationships of the isolates were investigated with molecular tests. Methods: Blood samples obtained from the patients in pediatric neonatal unit were studied with automatized blood culture [BacT/Alert (Bio Merioux, France)]. Yeast isolates from environmental surveillance cultures (TPN solutions, hands of healthcare personnel, etagere, etc) and patients were identified as C. albicans with conventional methods and ID 32 C and ATB (TM) Fungus 3 (Biomerieux, France) kits. Clonal similarity was determined by using AP-PCR as initial method and we have also typified all strains by the method of REP-PCR (diversilab system, bioMerieux). Finally; Pulsed Field Gel Electrophoresis (PFGE) was used for confirmation. Results: C. albicans was isolated in blood cultures of seven patients. Similar antifungal susceptibility patterns were observed in all isolates. AP-PCR and REP-PCR showed that the C. albicans isolates grown in the TPN solution and from the patients- blood cultures were clonally same strains. PFGE analysis further confirmed this clonality. Conclusion: According to results of the molecular methods, we thought that a C. albicans outbreak had occurred in the neonatal pediatric unit, due to contamination of TPN solution.